Materials, productions, exchange network and their impact on the societies of Neolithic Europe ; proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain).: proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain). Session A25a / Volume 13, ([2017]) - Guilaine, Jean
No abstract available